2016
DOI: 10.1101/038315
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How transposons drive evolution of virulence in a fungal pathogen

Abstract: Genomic plasticity enables adaptation to changing environments, which is especially relevant for pathogens that engage in arms races with their hosts. In many pathogens, genes mediating aggressiveness cluster in highly variable, transposon-rich, physically distinct genomic compartments. However, understanding of the evolution of these compartments, and the role of transposons therein, remains limited. We now show that transposons are the major driving force for adaptive genome evolution in the fungal plant pat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 85 publications
(178 reference statements)
7
22
0
Order By: Relevance
“…However, the few genes present in the lineage-specific regions are enriched in plant-induced genes, including genes encoding effectors and determinants of host specificity [56,57]. Faino and co-workers investigated the origin of the lineage-specific fragments using whole-genome assemblies obtained by single molecule real-time sequencing [58]. They showed that lineagespecific fragments are generated mainly by segmental genomic duplications followed by extensive sequence divergence.…”
Section: Example 2: Hybridization Of Crop Plants Driving Hybrid Specimentioning
confidence: 99%
“…However, the few genes present in the lineage-specific regions are enriched in plant-induced genes, including genes encoding effectors and determinants of host specificity [56,57]. Faino and co-workers investigated the origin of the lineage-specific fragments using whole-genome assemblies obtained by single molecule real-time sequencing [58]. They showed that lineagespecific fragments are generated mainly by segmental genomic duplications followed by extensive sequence divergence.…”
Section: Example 2: Hybridization Of Crop Plants Driving Hybrid Specimentioning
confidence: 99%
“…Subsequently, nested-PCR primers were designed and optimized for specific detection of D and ND pathotypes in planta and in soil samples (Mercado-Blanco et al 2002;Pérez-Artés et al 2005). However, although these primers have worked for several isolates tested worldwide, it was found that they do not produce the desired amplicon on all V. dahliae isolates (Collins et al 2005), which may be explained by the high genetic variability that exists among V. dahliae isolates (De Jonge et al 2012Faino et al 2015Faino et al , 2016. Arguably, genetic differences between V. dahliae isolates are underlying their behaviour as D or as ND, and the most reliable molecular marker would be a marker on the gene(s) that is (are) responsible for the differential disease phenotype.…”
Section: Genetic Diversity and Detection Of V Dahliaementioning
confidence: 96%
“…changes in the number of chromosomes within a nucleus, and to chromosomal rearrangements (3)(4)(5). While these processes have been often associated with disease development (6), they can also provide genetic diversity that is beneficial for adaptation to novel or changing environments (7,8). For example, aneuploidy in the budding yeast Saccharomyces cerevisiae can lead to increased fitness under selective conditions, such as the presence of antifungal drugs (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances in long-read sequencing technologies enables to study the constitution and evolution of centromeres (11,16,(29)(30)(31). By using long-read sequencing technologies in combination with optical mapping, we previously generated gapless genome assemblies of two strains of the fungal plant pathogen Verticillium dahliae (32), whose genomes are characterized by genome rearrangements and the occurrence of lineage-specific (LS) regions (7,8,(33)(34)(35)) that are hypervariable between V. dahliae strains and contain genes with roles in adaptive evolution to plant hosts (7,8,33,35).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation